Implementasi Metode Port Knocking pada MikroTik RouterOS untuk Mendukung Keamanan Jaringan - Fadhlirrahman Baso; Muhammad Ardiansyah (PT. Lontara Digitech Indonesia, 2023)
This study aims to implement the Port Knocking security method in a local network using MikroTik RouterOS. The Port Knocking method is employed to enhance system security by closing access to specific ports in the network and only allowing access to these ports when a predefined sequence of port knocks is performed. The research encompasses several stages, including the analysis of the port data to be tested, the configuration of the MikroTik router, and the security system testing. The results of this study demonstrate the successful securing of the Winbox and WWW ports on the MikroTik server using the Port Knocking method. Users are required to execute the predetermined port knocking sequence before accessing these services. Furthermore, the Port Knocking method effectively blocks ping access to the MikroTik server for users who have not completed the authentication process. These findings indicate that the implementation of the Port Knocking method significantly enhances the local network security on the MikroTik server.